(untitled) (Global Journals of Research in Engineering, 2014)
In this paper cell range for different region and modulation schemes has been calculated for WiMAX and 3G mobile technologies, considering both as a cellular mobile technology. While resolving the cell range using different propagation models, effect of various parameters like frequency, base station antenna height, transmitting power, maximum allowable path loss and SNR over cell range have also been studied. Analysis has been done for both uplink and downlink. From the study it reveals that for downlink, cell range increases with increasing transmitting power and decreases with frequency and SNR. For uplink, cell range decreases with SNR. When adaptive modulation advances, it affects cell range significantly for parameters such as frequency, base antenna height and SNR.